Efeitos das condições de queima e densidade aparente sobre a sobrequeima em porcelanatos - Contartesi, Flavia (2015)
The phenomenon of overfiring manifests in porcelain tiles and other products with high degree of vitrification, as a consequence of the expansion of gases trapped in closed pores, in the final stages of sintering. When it is not properly controlled, it generates swelling of the pieces and then they present dimensional problems, damages in the mechanical properties and low stain resistance in polished products. Porcelain tiles are products with strict requirements, water absorption ≤0.5% for glazed and ≤0.1% for technical ones, moreover the ceramics industries, nowadays, use firing cycles increasingly faster, which allows significant productivity increases and costs reductions. Associate both avoiding the phenomenon of overfiring is not an easy task. The aim of this study was to evaluate the effects of the green bulk density and the firing curve (heating rate and soaking time at the maximum temperature) on the characteristics of the final product and on the development of this phenomenon. To achieve the objectives, a factorial design of experiments (DOE) was used. The differences between the firing temperatures necessary to produce 0.5% of water absorption and to achieve the maximum bulk density were considered to determine the firing range before overfiring the porcelain tiles. The results indicate that the firing range is strongly influenced by the time the samples were kept at the maximum temperature of the firing cycle. At the same time, they also indicate the importance of the bulk density of the green bodies as a way to reduce the closed porosity of the fired bodies and consequently to prevent the production of overfired porcelain tiles.